A CROSS SECTIONAL STUDY QUALITY OF LIFE PEOPLE LIVING WITH HIV&AIDS: EMPHASIZE IN ANTHROPOMETRIC VALUE - Walewangko, Olivia Cicilia (Acta Interna The Journal of Internal Medicine, 2012)
ABSTRACTBackground. The nutritional problem is a significant role factor in determine of health, mortality and quality of life of people with HIV&AIDS. Therefore, it is very important to provide the nutritional assessment, nutritional management, counseling and education which are very useful to upgrade the quality of life of people with HIV&AIDS.Objective. This study was designed to analyze the correlation between anthropometric measurement with quality of life of people with HIV&AIDS.Method. The study design was a cross sectional study. The subjects were HIV&AIDS patients who came to outpatient clinic in Dr. Sardjito General Hospital Yogyakarta, from November 2009 â January 2010. Subjects eligible with inclusion criteria were examined for anthropometric measurement and fill the WHOQOL-bref questioner.Result. There were 53 subjects eligible to the study criteria from November 2009 to January 2010. Majority of the subjects were man (73.6%), single (62.3%) and live alone (58.5%), last education was high school (41.5%) and employed (73.6%). Mean of ages was 33 years old, weight 53.67Â±10.3kg, height 161.28Â±7.68cm, BMI 20.57Â± 3.48 Kg/m2, MUAC 24.40 Â± 3.23 cm, waist circumference 76.17 Â± 8.10 cm, hip circumference 87.04 Â± 8.03 cm , ST 11.17 Â± 8.10 mm. Mean score of total WHOQOL-bref was 75.68 Â± 10.3, Domain 1 (physics) 21.32 Â± 3.07, Domain 2 (psychology) 19.75 Â± 3.62 , Domain 3 (social) 10.04 Â± 1.87, Domain 4 (environment) 24.75 Â± 4.58. There was a very weak correlation between anthropometric measurements with quality of life; with the p value was statistically insignificant.Conclusion. There was no significant correlation between nutritional statuses which is measured by the anthropometric value with the quality of life in people with HIV&AIDS.Â Keywords: HIV, nutrition, anthropometric, QOLÂ